Analisis Pelanggaran Asas Pacta Sunt Servanda dalam Kasus Gagal Bayar PT. Asuransi Jiwasraya - Maksimiliane Kolorian Hilem; Orpa Juliana Nubatonis; Chatryen M. Dju Bire (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research is a research that aims to find out and analyze the violation of the principle of pacta sunt servanda in the case of PT Asuransi Jiwasraya's default on legal protection for policyholders. This research is a normative research supported by a legislative approach, a conceptual approach and a case approach using primary legal materials and secondary legal materials collected using literature study techniques after which they are analyzed in a qualitative descriptive manner. The results of the study show that the factors that cause the violation of the principles of Pacta Sunt Servanda in the Case of PT Asuransi Jiwasraya Default are poor corporate governance, investment in high-risk instruments, financial irregularities and weak financial management, stock price engineering, and weak application of the prudential principle in investing.